A chemical-mechanics model for the mechanics deterioration of pervious concrete subjected to sulfate attack. (20th December 2021) - Song, Hui; Yao, Jinwei; Luo, Yuming; Gui, Faliang
Highlights: The strength of pervious concrete subjected to sulfate attack were tested. A prediction model for the compression strength was promoted. Compressive strength is related to filling of chemical products and expansion stress. Abstract: Strength deterioration is one of the primary indicators to reduce the durability of pervious concrete under sulfate attack. This study aimed to establish a chemical–mechanical model to predict the strength evolution. The compressive strength and splitting tensile strength of pervious concrete in three different concentrations of sodium sulfate solution were obtained by experiments. A corrosion coefficient was adopted to evaluate the deterioration of compressive strength. The corrosion coefficient model was developed by considering the pore filling effect of expansion products and the corrosion damage induced by expansion stress. Compared with the experimental results, the developed model could better characterize the deterioration process of pervious concrete. Therefore, the model proposed in this paper provides a more reliable solution for the design and durability life assessment of pervious pavement engineering in sponge city construction projects.